Modification of Mantle Cargo by Turbulent Ascent of Kimberlite - Jones, Thomas J.; Russell, James K.; Sasse, David (Frontiers in Earth Science, 2019)
Kimberlite magmas provide transport for cratonic mantle xenoliths and diamonds to the Earth's surface. However, the mechanisms supporting the successful and efficient ascent of these dense cargo-laden magmas remains enigmatic due to the absence of historic eruptions, uncertainties in melt composition, and questions concerning their rheology. Mantle-derived xenocrystic olivine is the most abundant component in kimberlite and is uniquely rounded and ellipsoidal in shape. Here, we present data from a series of novel attrition experiments designed to inform on the transport of low-viscosity melts through the mantle lithosphere. The experimental data suggest that the textural properties of the mantle-derived olivine are records of the flow regime, particle concentration, and transport duration of ascent for kimberlitic magmas. Specifically, our results provide evidence for the rapid and turbulent ascent of kimberlite during their transit through the lithosphere; this transport regime creates particle-particle interactions that continually modify the mantle cargo and facilitate mineral assimilation.